2004
DOI: 10.1207/s15327914nc4901_8
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Clinical Study of Short-Term Isoflavone Supplements in Breast Cancer Patients

Abstract: Many laboratory-based studies have shown that soy can suppress breast cancer proliferation. However, given the recent controversy generated by animal experiments that soy may under certain conditions stimulate breast cancer growth, we decided to carry out a pilot clinical trial in order to elucidate any interaction(s) between short-term isoflavone supplement administration and breast cancer growth. After a core-needle biopsy established the diagnosis of breast cancer, 17 patients were administered soy isoflavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 19 publications
2
37
0
1
Order By: Relevance
“…De récentes études ont montré que ni les protéines de soja, ni les aliments au soja, ni les compléments alimentaires d'isoflavones n'ont d'effet sur des marqueurs du risque de cancer du sein comme la densité mammographique (Hooper, 2010 ;Wu, 2015) ou la prolifération des cellules mammaires (Khan et al, 2012 ;Palomares, 2004 ;Sartippour, 2004 ;Shike, 2014).…”
Section: En Cas D'antécédents De Cancer Du Seinunclassified
“…De récentes études ont montré que ni les protéines de soja, ni les aliments au soja, ni les compléments alimentaires d'isoflavones n'ont d'effet sur des marqueurs du risque de cancer du sein comme la densité mammographique (Hooper, 2010 ;Wu, 2015) ou la prolifération des cellules mammaires (Khan et al, 2012 ;Palomares, 2004 ;Sartippour, 2004 ;Shike, 2014).…”
Section: En Cas D'antécédents De Cancer Du Seinunclassified
“…41 One study found that supplementation with 200 mg of soy isoflavones daily over two to six weeks before breast cancer surgery showed a nonsignificant trend toward inhibition of cancer growth compared with a control group. 43 A meta-analysis of five prospective cohort studies from the United States and China found that high consumption of soy protein or soy isoflavones after breast cancer diagnosis was associated with a 26% decrease in recurrence (HR 0.74, 95% CI 0.61-0.85) and a 16% reduction in breast cancer mortality (HR 0.84, 95% CI 0.71-0.99) compared with low consumption. 44 Another meta-analysis of four prospective cohort studies, two of which were included in the previous analysis, found a 16% reduced risk of recurrence among women consuming high levels of soy isoflavone (RR 0.84, 95% CI 0.65-0.86), with no significant heterogeneity among the studies.…”
Section: Soymentioning
confidence: 99%
“…Around the globe federal and government efforts have accumulated on consensus for statutory policy to use nutraceuticals on their daily requirements, supplementation, combinations and dosage to prevent or manage the cancer [79][80][81][82][83]. Randomized and double blind control trials indicated the increased importance of vitamins, herbs and fresh vegetables as likely protective supplements [84][85][86][87][88][89][90], tomato (lycopene) in prostate cancer prevention [91][92][93], nutritional intervention in different cancers of different body organs in the body [94][95][96][97][98][99][100]. New concept of Mediterranean diet was introduced to reduce the risk of cancer along with cardioprotection [101][102][103][104].…”
Section: Nutraceuticals In Cancer Prevention During Years 2002-2008mentioning
confidence: 99%